(untitled) (Global Journal of Management and Business Research, 2020)
This paper study the determinants of the gender gap in Cameroonian labor market and its causal impact on socioprofessional mobility as well as they active itself and its family by using EISS 2 database of SNI. We use dichotomy probit models with propensity score matching, notably nearest neighbor and Kernel density method of estimation for overcome heterogeneity and selection bias so that our result either robust. By putting in evidences the spatial and gender heterogeneities, we fund that urban females and young girl#x2019;s activities economics levels has a meaningfully impact on the socio-professional mobility of active female and on its family.